Numerical simulation of an incompressible laminar flow in a square lid-driven cavity - Eisermann, Jonatan Ismael (2024)
A numerical simulation of an incompressible laminar flow inside a lid-driven square cavity is carried out in this work. For this purpose, a two-dimensional mathematical model based on the vorticity-stream function formulation of the Navier-Stokes equations is deduced and then discretized on a computational mesh using the Finite Differences method. For the resolution of the discretized equations from the initial and boundary conditions of the problem, a computational code based on a semi-implicit iterative process is implemented in the Matlab software and is available in the text. From this code, simulations are made for incompressible flows with Reynolds numbers 100, 400 and 1000. The code validation is done through comparisons of numerical results obtained with reference results available in the literature. Analyzes resulting from the simulation show that the flows cause the creation of a large recirculation zone near the center of the cavity and two smaller ones in the lower corners, whose intensity and size depend directly on the corresponding Reynolds number.